1999
DOI: 10.1021/la9810915
|View full text |Cite
|
Sign up to set email alerts
|

Surface Reactivity at “Chiral” Platinum Surfaces

Abstract: The electro-oxidation of D-and L-glucose has been investigated using the chiral electrode Pt{643} R and its enantiomorph Pt{643} S . Both electrodes are demonstrated to be enantioselective. We ascribe this behavior to the inherent (left or right) "handedness" of kink sites present at the surface. In contrast, no difference in D-and L-glucose oxidation could be detected using stepped Pt{211} and Pt{332} electrodes. Stepped surfaces are achiral, since they lack the prerequisite necessary for the observation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
303
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(311 citation statements)
references
References 24 publications
8
303
0
Order By: Relevance
“…This was first tested in UHV by Gellman and coworkers [179], who found later enantiospecific differences in thermal desorption spectra [180]. The first distinct enantioselective reaction, however, was found for electro-oxidation of glucose over Pt(543) [181]. Also noteworthy is the enantioselective interaction of cysteine with kinks on gold surfaces [182][183][184].…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 99%
“…This was first tested in UHV by Gellman and coworkers [179], who found later enantiospecific differences in thermal desorption spectra [180]. The first distinct enantioselective reaction, however, was found for electro-oxidation of glucose over Pt(543) [181]. Also noteworthy is the enantioselective interaction of cysteine with kinks on gold surfaces [182][183][184].…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 99%
“…Cyclic voltammetry has been used to study the electrooxidation kinetics of glucose and other sugars on an array of naturally chiral platinum electrode surfaces in aqueous solutions. [44,[54][55][56] These studies have shown that the rates of D-glucose and L-glucose oxidation on naturally chiral Pt electrodes can differ by as much as a factor of three. As in the case of enantioselective hydrogenation on the chirally templated Pt catalysts, the enantioselectivities of glucose oxidation are influenced by the presence of modifiers adsorbed from solutions.…”
Section: Enantioselectivity Of Naturally Chiral Metal Surfacesmentioning
confidence: 99%
“…Each kink is formed by the intersection of three low Miller index microfacets ({111}, {100}, and {110}) with different structures. [44] The chirality of the kink arises from the sense of rotational progression among the three microfacets when viewed from above the surface. Like chiral molecules, the handedness of chiral surfaces can be denoted by using a modified Cahn-Ingold-Prelog convention based on microfacet priority.…”
Section: Chiral Surfaces From Achiral Bulk Crystal Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been produced by decorating the surfaces of achiral substrates by chiral molecules, or by introducing defects in the single crystals which exposes chiral kink sites. [6][7][8][9][10][11][12][13][14][15][16][17] It was shown that chiral surfaces can also be produced by electrodeposition technique. [18,19] Unlike other vacuum techniques, electrodeposition is cheaper and can be carried out at ambient conditions.…”
Section: Introductionmentioning
confidence: 99%